Risk prediction of all-cause mortality in hospitalized patients with severe acute pancreatitis by serum urea nitrogen/albumin ratio - Huisi Qiu; Yongshuai Fu; Ziwen Lv; Xingyu Zhu; Junhui Gu; Zhuo Gao; Dong Liu (PLoS ONE, 2025)
Background Classification of risk levels in patients with acute pancreatitis remains a difficult task. Although some biomarkers have emerged to predict the prognosis of patients with acute pancreatitis, they have not been widely used in clinical practice for several reasons. This study aimed to investigate the correlation between the serum urea nitrogen-to-albumin ratio (BAR) and the mortality risk in ICU patients with acute pancreatitis. Method This was a retrospective study. Data were collected from the Medical Information Mart for Intensive Care IV (MIMIC IV 2.0). The primary outcome was in-hospital mortality in the patients with severe acute pancreatitis. In this study, multivariate logistic proportional regression analysis and restricted cubic spline regression were used to evaluate the association between serum urea nitrogen/albumin ratio and in-hospital mortality in patients with severe acute pancreatitis. In the sensitivity analysis, the Boruta and random forest algorithms were used to determine the feature importance of the serum urea nitrogen to albumin ratio, and subgroup analysis was used to explore the robustness of the results. Result 726 patients were included in this study. The in-hospital mortality rate was 11.85%. Multivariate logistic regression analysis revealed that BAR was independently associated with an increased risk of in-hospital mortality (odds ratio [HR], 1.081 [95% confidence interval [CI], 1.062–1.101]; P < 0.001). The restricted cubic spline regression model revealed that the risk of in-hospital mortality increased linearly with increasing BAR. Sensitivity analysis indicated that the results were stable. Additionally, the machine learning results suggested that the serum urea nitrogen to albumin ratio is an important feature for the outcomes of severe acute pancreatitis. Conclusion A high serum urea nitrogen to albumin ratio was significantly associated with in-hospital mortality in patients with severe acute pancreatitis.